Tissue-engineered cellulose tubes for microvascular and lymphatic reconstruction: A translational and feasibility study - Will-Marks, Patrick; Taqatqeh, F.; Fricke, Fabia; Berner, J. E.; Lindenblatt, N.; Kneser, Ulrich; Hirche, Christoph (Journal of plastic, reconstructive & aesthetic surgery, 2024)
Background - Lymphedema microsurgery is an emerging treatment modality, with dissimilar long-term outcomes. One of the main technical challenges in lymphatic microsurgery is the identification and availability of suitable donor vessels for anastomosis. Tissue engineering using biomaterials has demonstrated promise in addressing vessel quality issues in other fields, but its application in microsurgery is still limited. - Methods - Decellularized cellulose tubes were developed and bioengineered by decellularizing stems of Taraxacum-Ruderalia. The microscopic structure, mechanical properties, and residual DNA content of the cellulose tubes were evaluated. Human and murine skin fibroblasts and dermal lymphatic endothelial cells were isolated and cultured for recellularization studies. Biocompatibility, proliferative capacity, and ex-vivo endothelialization of the cellulose tubes were assessed as potential interposition grafts. Finally, the engineered cellulose tubes were assessed as interposing xenografts for lymphovenous anastomoses (LVA) in an ex-vivo swine limb model. - Results - The decellularized cellulose tubes exhibited a suitable microscopic structure, mechanical properties, and low residual DNA content. The tubes showed adequate biocompatibility, supported cell proliferation, and facilitated spontaneous ex-vivo endothelialization of lymphatic endothelial cells. In the swine limb model, LVA using the engineered cellulose tubes was successfully performed. - Conclusion - This translational study presents the use of decellularized cellulose tubes as an adjunct for micro and supermicrosurgical reconstruction. The developed tubes demonstrated favorable structural, mechanical, and biocompatible properties, making them a potential candidate for improving long-term outcomes in lymphedema surgical treatment. The next translational step would be trialing the obtained tubes in a microsurgical in-vivo model.
Online verfügbar: 13. Juni 2024, Artikelversion: 20. August 2024
Gesehen am 06.11.2024